Antistatic high-thermal-conductivity adhesive tape and manufacturing method thereof
By synthesizing anionic polymer and anionic nanoboronitride and working with Al3+, a high-thermal resistance and electrostatic adhesive is prepared, which solves the shortcomings of existing thermal conductivity and viscosity balance and electrostatic problems of existing thermal tapes, and realizes the preparation of anti-static and high-thermal conductive tapes to protect the performance of optoelectronic materials and devices.
Patent Information
- Application Number
- CN202510203901.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-22
AI Technical Summary
The existing thermal tape has shortcomings in balancing thermal conductivity and viscosity, and is prone to static electricity during use, damaging optoelectronic materials and devices.
By synthesizing anionic polymer and anionic nanoboronitride and working with Al3+, a high thermal conductivity and anti-static adhesive was prepared, combined with PET substrate and silicone oil release agent to make anti-static and highly thermally conductive tape.
It achieves an effective balance between thermal conductivity and viscosity of the tape, and at the same time has good antistatic properties, which can better protect optoelectronic materials and devices.
Smart Images

Figure CN119859480A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, relates to an antistatic and high thermal conductive adhesive tape, and also relates to a method for preparing the antistatic and high thermal conductive adhesive tape. Background Art
[0002] Optoelectronic materials and devices (LED (light-emitting diode), OLED (organic light-emitting diode), chips, ion batteries, artificial intelligence) are increasingly used. They usually generate a lot of heat when used. The energy utilization efficiency of optoelectronic materials and devices decreases with the increase of temperature. Long-term high-temperature operation leads to a decrease in device life, increased energy consumption, and also brings safety hazards. Constructing a high thermal conductivity tape can effectively solve this problem. The preparation of traditional thermal conductive tapes is mainly to add metal oxides, graphite, etc. with good thermal conductivity to the adhesive resin, and then prepare the tape through a coating process. As we all know, the viscosity of the tape mainly depends on the resin, while the conductivity mainly depends on metal oxides or graphene. When the two are compounded, the viscosity and thermal conductivity of the tape cannot be effectively balanced. In addition, optoelectronic materials and devices must not only solve the problem of thermal management, but also solve the damage to the device caused by static electricity during use. Therefore, it is necessary to prepare an antistatic, high thermal conductivity and high viscosity tape. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing an antistatic and high thermal conductive adhesive tape, wherein the adhesive tape prepared by the method can meet the requirements of good thermal conductivity and high viscosity, and at the same time has antistatic properties.
[0004] Another object of the present invention is to provide an antistatic and highly thermally conductive adhesive tape.
[0005] The first technical solution adopted by the present invention is a method for preparing an antistatic and high thermal conductive tape, which specifically comprises the following steps: Step 1, synthesizing anionic polymer; Step 2, synthesizing anionic nano boron nitride; Step 3, synthesizing a high thermal conductivity antistatic adhesive according to the products obtained in step 1 and step 2; Step 4, synthesizing an antistatic adhesive according to the product obtained in step 3; Step 5, making a tape according to the antistatic adhesive obtained in step 4.
[0006] The first technical solution of the present invention is also characterized in that: The specific process of step 1 is: Take 0.5-1g of vinyl benzoic acid, 0.5-1mL of acrylic acid, 0.05-0.1mL of triacrylate, 2-3mL of ethylene glycol phenyl ether acrylate, and 2-3mL of 2-hydroxyethyl acrylate, add them to 3-5mL of isooctyl acrylate, stir evenly, then add 10-15mg of azobisisobutyronitrile to obtain a mixed solution, and put the obtained mixed solution into 60-80 o The mixture was reacted in an oil bath for 30-60 minutes, the viscosity was controlled at 5000-15000 cps, and the heating was stopped to obtain an anionic polymer.
[0007] The specific process of step 2 is: Step 2.1, add 5-10g of boric acid and 30-60g of urea to 100-200mL of a mixture of methanol and water, and heat the mixture to 80-100°C. o C, stirring, reacting for 20-30 min, filtering while hot after the reaction is completed, cooling the collected solution, and standing for 48-72 h to precipitate a white solid; Step 2.2, the product obtained in step 2.1 is filtered, and o Wash with ice water at 45-60 °C o C was dried overnight to obtain white crystals; Step 2.3, grind the white crystals obtained in step 2.2 in a mortar for 10-15 minutes, then put them into a tube furnace and gradually raise the temperature from room temperature to 900-1000 °C in ammonia carrier gas. o C, the temperature reaches 900-1000 o C and then kept warm for 3-6 h, and then the sample was cooled to room temperature in the furnace to obtain nano boron nitride; Step 2.4, disperse 0.5-1g of nano-boron nitride in 20-30 mL of anhydrous tetrahydrofuran solution, then add 0.05-0.1g of sodium naphthyl, stir in nitrogen and ice water bath for 24-48h to activate the nano-boron nitride, add 1-2mL of sodium acrylate monomer, and continue stirring for 36-48h to obtain sodium polyacrylate modified nano-boron nitride, also known as anionic nano-boron nitride.
[0008] The specific process of step 3 is: Step 3.1, taking 0.3-0.6 g of anionic polymer and dispersing it in 2-3 mL of aqueous solution, then adding 1.2-2.4 g of anionic nano-boron nitride, stirring evenly to obtain a polymer solution; Step 3.2, dissolving 0.2-0.4 g of aluminum trichloride in 2-4 mL of an aqueous solution to obtain an aluminum trichloride solution; Step 3.3, add the aluminum chloride solution obtained in step 3.2 dropwise to the polymer solution obtained in step 3.1, stirring at room temperature while adding, the dropping time is 30-45 minutes, and then add 10-15 mg of BPO and continue stirring at room temperature for 2-3 hours to obtain a high thermal conductive antistatic adhesive.
[0009] The specific process of step 4 is: dispersing the antistatic polymer in 2-3 mL of aqueous solution, then adding 10-15 mg of BPO and continuing to stir at room temperature for 2-3 hours to obtain an antistatic adhesive.
[0010] In step 4, the preparation process of the antistatic polymer is as follows: 2-4 mL of benzyl vinyl trimethyl ammonium chloride, 0.5-1 mL of triacrylate, 1-2 mL of ethylene glycol phenyl ether acrylate and 1-2 mL of 2-hydroxyethyl acrylate are added to 1-2 mL of isooctyl acrylate, stirred evenly, and then 10-15 mg of azobisisobutyronitrile is added, and the resulting mixed solution is placed in 60-80 o The reaction was carried out in an oil bath pot C for 60-120 minutes, the viscosity was controlled at 20000-30000 cps, and the heating was stopped to obtain an antistatic polymer.
[0011] The specific process of step 5 is: Step 5.1, a layer of antistatic adhesive prepared in step 4 is coated on the lower surface of the PET substrate with a coating thickness of 20-30um, and then the coating is passed through 60-80 o C drying for 1-2h and 365nm UV curing for 90-120s; Step 5.2: Apply a layer of double-terminal hydroxypropyl silicone release agent on the upper surface of the PET substrate with a thickness of 10-20um and 120-130 o C is cured to form a release layer; Step 5.3, coating the high thermal conductivity antistatic adhesive prepared in step 3 on the upper surface of the release layer prepared in step 5.2, with a coating thickness of 50-60 um, and o C and dried for 1-2 hours to form an antistatic heat-conductive layer to obtain an adhesive tape.
[0012] The second technical solution adopted by the present invention is that the antistatic and high thermal conductive tape is made by adopting the above-mentioned method for making the antistatic and high thermal conductive tape.
[0013] The beneficial effect of the present invention is that the present invention constructs anionic polymer resin and anionic nano boron nitride, and combines with Al 3+ Through the combined action of anions and cations, the adhesiveness and thermal conductivity of the tape are balanced. 3+As a counteracting agent for the cations and anions in resins and boron nitride, it strengthens the coordination between resin and boron nitride, and improves the adhesiveness and antistatic effect of the tape. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a schematic diagram of the structure of an adhesive tape made by the method for making an antistatic and high thermal conductive adhesive tape of the present invention; Figure 2 It is the thermal weight loss diagram of Example 1 and Comparative Examples 1, 2 and 4 of the method for making the antistatic and high thermal conductive tape of the present invention. DETAILED DESCRIPTION
[0015] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0016] The method for making the antistatic and high thermal conductive tape of the present invention specifically comprises the following steps: Step 1, synthesis of anionic polymer, specifically: Take 0.5-1g of vinyl benzoic acid, 0.5-1mL of acrylic acid, 0.05-0.1mL of triacrylate, 2-3mL of ethylene glycol phenyl ether acrylate and 2-3mL of 2-hydroxyethyl acrylate, add to 3-5mL of isooctyl acrylate, stir evenly, add 10-15mg of azobisisobutyronitrile to obtain a mixed solution, and put the obtained mixed solution into 60-80 o The mixture was reacted in an oil bath for 30-60 minutes, the viscosity was controlled at 5000-15000 cps, and the heating was stopped to obtain an anionic polymer.
[0017] Step 2, synthesis of anionic nano boron nitride, specifically: Take 5-10g of boric acid and 30-60g of urea and add them to 100-200mL of methanol and water (volume v:v=1:1) mixed solution, heat the temperature to 80-100 o C. Stirring to fully dissolve the raw materials, continue stirring and reacting for 20-30 minutes. After the reaction is completed, filter while hot. After the collected solution is cooled, stand for 48-72 hours to precipitate white solid. Then filter, 0 o Wash with ice water at 45-60 °C o C and dried overnight to obtain white crystals. The obtained white crystals were ground in a mortar for 10-15 minutes, then placed in a tube furnace and gradually heated from room temperature to 900-1000 C in an ammonia carrier gas. o C (heating rate is 10 o C / min), the temperature reaches 900-1000 oC and then kept warm for 3-6 hours, and then the sample was cooled to room temperature with the furnace to obtain nano boron nitride. 0.5-1g of nano boron nitride was dispersed in 20-30 mL of anhydrous tetrahydrofuran solution, and then 0.05-0.1g of sodium naphthalene was added, and the nano boron nitride was activated by stirring in nitrogen and ice water bath for 24-48 hours, and 1-2mL of sodium acrylate monomer was further added, and stirring was continued for 36-48 hours to obtain polyacrylic acid modified nano boron nitride, also known as anionic nano boron nitride.
[0018] Step 3, synthesis of high thermal conductivity antistatic adhesive, specifically: Take 0.3-0.6g of anionic polymer and disperse it in 2-3mL of aqueous solution, then add 1.2-2.4g of anionic nano boron nitride and stir evenly to obtain a polymer solution. Then take 0.2-0.4g of aluminum chloride and dissolve it in 2-4mL of aqueous solution to obtain an aluminum chloride solution; add the aluminum chloride solution drop by drop to the polymer solution, stirring at room temperature while adding, the dropping time is 30-45min, then add 10-15mg of BPO (benzoyl peroxide) and continue stirring at room temperature for 2-3h to obtain a high thermal conductivity antistatic adhesive for standby use.
[0019] Step 4, the synthesis of the antistatic adhesive, is specifically: Take 2-4 mL of benzyl vinyl trimethyl ammonium chloride, 0.5-1 mL of glycerol triacrylate, 1-2 mL of ethylene glycol phenyl ether acrylate and 1-2 mL of 2-hydroxyethyl acrylate, add them to 1-2 mL of isooctyl acrylate, stir evenly, then add 10-15 mg of azobisisobutyronitrile to obtain a mixed solution, and place the obtained mixed solution in a 60-80 o The reaction was carried out in an oil bath pot C for 60-120 minutes, the viscosity was controlled at 20000-30000 cps, and the heating was stopped to obtain an antistatic polymer. The antistatic polymer was dispersed in 2-3 mL of aqueous solution, and then 10-15 mg of BPO was added and stirred at room temperature for 2-3 hours to obtain an antistatic adhesive for standby use.
[0020] Step 5, preparation of the tape, specifically: Take a 10x10cm PET (polyethylene terephthalate) substrate, first apply a layer of antistatic adhesive on the lower surface of the PET substrate with a coating thickness of 20-30um, and then o C for 1-2h and 365nm UV curing for 90-120s. Then, a layer of silicone release agent (double-terminal hydroxypropyl silicone oil, thickness of 10-20um) was applied on the upper surface of the PET substrate, 120-130 o Finally, a high thermal conductivity antistatic adhesive is coated on the upper surface of the release layer with a coating thickness of 50-60um and at 45-55o C and dried for 1-2 hours to form an antistatic heat-conductive layer to obtain an adhesive tape.
[0021] Example 1 The method for making the antistatic and high thermal conductive tape of the present invention specifically comprises the following steps: Step 1, synthesis of anionic polymer, specifically: Take 0.5 g of vinyl benzoic acid, 0.5 mL of acrylic acid, 0.05 mL of triacrylate, 2 mL of ethylene glycol phenyl ether acrylate and 2 mL of 2-hydroxyethyl acrylate, add them to 3 mL of isooctyl acrylate, stir evenly, then add 10 mg of azobisisobutyronitrile, and put the resulting mixed solution into 60 o The mixture was reacted in an oil bath for 30 min, the viscosity was controlled at 5000-15000 cps, and the heating was stopped to obtain an anionic polymer.
[0022] Step 2, synthesis of anionic nano boron nitride, specifically: Take 5g of boric acid and 30g of urea and add them to 100mL of a mixture of methanol and water (v:v=1:1) and heat the mixture to 80 o C to fully dissolve the raw materials, continue stirring and reacting for 20 minutes, filter while hot after the reaction is completed, and let the collected solution stand for 48 hours after cooling to precipitate white solid. Then filter, 0 o Wash with ice water at 45°C o After drying overnight at 370 °C, white crystals were obtained. The obtained white crystals were ground in a mortar for 10 min, then placed in a tube furnace, and the temperature was gradually raised from room temperature to 900 °C in an ammonia carrier gas. o C (heating rate is 10 o C / min), the temperature reaches 900 o C and then kept warm for 3 hours, and then the sample was cooled to room temperature with the furnace to obtain nano boron nitride. 0.5g of nano boron nitride was dispersed in 20mL of anhydrous tetrahydrofuran solution, and then 0.05g of sodium naphthalene was added, and the nano boron nitride was activated by stirring in nitrogen and ice water bath for 24 hours, and 1mL of sodium acrylate monomer was further added, and stirring was continued for 36 hours. Polyacrylic acid modified nano boron nitride, also known as anionic nano boron nitride, was obtained.
[0023] Step 3, synthesis of high thermal conductivity antistatic adhesive, specifically: Take 0.3g of anionic polymer and disperse it in 2mL of aqueous solution, then add 1.2g of anionic nano boron nitride and stir evenly to obtain a polymer solution. Then take 0.2g of aluminum chloride and dissolve it in 2mL of aqueous solution to obtain an aluminum chloride solution, and add the aluminum chloride solution drop by drop to the polymer solution, stirring at room temperature while adding, and the dropping time is 30min. Then add 10mg of BPO and continue stirring at room temperature for 2h to obtain a high thermal conductivity antistatic adhesive for standby use.
[0024] Step 4, the synthesis of the antistatic adhesive, is specifically: Take 2 mL of benzyl vinyl trimethyl ammonium chloride, 0.5 mL of glycerol triacrylate, 1 mL of ethylene glycol phenyl ether acrylate, and 1 mL of 2-hydroxyethyl acrylate, add them to 1 mL of isooctyl acrylate, stir evenly, and then add 10 mg of azobisisobutyronitrile. Put the resulting mixed solution into 60 o The reaction was carried out in a C oil bath for 60 minutes, the viscosity was controlled at 20000-30000 cps, and the heating was stopped to obtain an antistatic polymer. The antistatic polymer was dispersed in 2 mL of aqueous solution, and then 10 mg of BPO was added and stirred at room temperature for 2 hours to obtain an antistatic adhesive for use.
[0025] Step 5, preparation of the tape, specifically: Take a 10x10cm PET substrate, first, apply a layer of antistatic adhesive on the lower surface of the PET substrate with a coating thickness of 20um, and then o C for 1 h and 365 nm UV curing for 90 s (to obtain an antistatic layer). Then, a layer of silicone release agent (thickness 10 μm) was coated on the upper surface of the PET substrate. o Finally, a high thermal conductivity antistatic adhesive was coated on the upper surface of the release layer with a coating thickness of 50 μm and heated at 45 o C and dried for 1 hour to form an antistatic thermal conductive layer, thus obtaining an adhesive tape; the structure of the adhesive tape is as follows Figure 1 shown.
[0026] Comparative Example 1 (without adding AlCl3, the antistatic property of the adhesive layer is reduced, and the viscosity is reduced) Step 1, synthesis of anionic polymer, specifically: Take 0.5 g of vinyl benzoic acid, 0.5 mL of acrylic acid, 0.05 mL of triacrylate, 2 mL of ethylene glycol phenyl ether acrylate and 2 mL of 2-hydroxyethyl acrylate, add them to 3 mL of isooctyl acrylate, stir evenly, add 10 mg of azobisisobutyronitrile, and put the resulting mixed solution into 60 o The mixture was reacted in an oil bath for 30 min, the viscosity was controlled at 5000-15000 cps, and the heating was stopped to obtain an anionic polymer.
[0027] Step 2, synthesis of anionic nano boron nitride, specifically: Take 5g of boric acid and 30g of urea and add them to 100mL of a mixture of methanol and water (v:v=1:1) and heat the mixture to 80 o C to fully dissolve the raw materials, continue stirring and reacting for 20 minutes, filter while hot after the reaction is completed, and let the collected solution stand for 48 hours after cooling to precipitate white solid. Then filter, 0 o Wash with ice water at 45°C o After drying overnight at 370 °C, white crystals were obtained. The obtained white crystals were ground in a mortar for 10 min, then placed in a tube furnace, and the temperature was gradually raised from room temperature to 900 °C in an ammonia carrier gas. o C (heating rate is 10 o C / min), the temperature reaches 900 o C and then kept warm for 3 hours, and then the sample was cooled to room temperature with the furnace to obtain nano boron nitride. 0.5g of nano boron nitride was dispersed in 20mL of anhydrous tetrahydrofuran solution, and then 0.05g of sodium naphthalene was added, and the nano boron nitride was activated by stirring in nitrogen and ice water bath for 24 hours, and 1mL of sodium acrylate monomer was further added, and stirring was continued for 36 hours. Polyacrylic acid modified nano boron nitride, also known as anionic nano boron nitride, was obtained.
[0028] Step 3, synthesis of high thermal conductivity antistatic adhesive, specifically: Take 0.3g of anionic polymer and disperse it in 2mL of aqueous solution, then add 1.2g of anionic nano-boron nitride and stir evenly to obtain a polymer solution. Then add 10mg of BPO and continue stirring at room temperature for 2h to obtain a high thermal conductivity antistatic adhesive for standby use.
[0029] Step 4, the synthesis of the antistatic adhesive, is specifically: Take 2 mL of benzyl vinyl trimethyl ammonium chloride, 0.5 mL of glycerol triacrylate, 1 mL of ethylene glycol phenyl ether acrylate and 1 mL of 2-hydroxyethyl acrylate, add them to 1 mL of isooctyl acrylate, stir evenly, add 10 mg of azobisisobutyronitrile, and put the resulting mixed solution into 60 o The reaction was carried out in a C oil bath for 60 minutes, the viscosity was controlled at 20000-30000 cps, and the heating was stopped to obtain an antistatic polymer. The antistatic polymer was dispersed in 2 mL of aqueous solution, and then 10 mg of BPO was added and stirred at room temperature for 2 hours to obtain an antistatic adhesive for use.
[0030] Step 5, preparation of the tape, specifically: Take a 10x10cm PET substrate, first, apply a layer of antistatic adhesive on the lower surface of the PET substrate with a coating thickness of 20um, and then o C for 1 h and 365 nm UV light for 90 s. Then, a layer of silicone release agent (thickness 10 μm) was coated on the upper surface of the PET substrate. o Finally, a high thermal conductivity antistatic adhesive was coated on the upper surface of the release layer with a coating thickness of 50 μm and heated at 45 o C and dried for 1 hour to form an antistatic thermal conductive layer to obtain an adhesive tape.
[0031] Comparative Example 2 (Nano-boron nitride was not anion-modified, the adhesive tape had reduced viscosity and reduced thermal conductivity) Step 1, synthesis of anionic polymer, specifically: Take 0.5 g of vinyl benzoic acid, 0.5 mL of acrylic acid, 0.05 mL of triacrylate, 2 mL of ethylene glycol phenyl ether acrylate and 2 mL of 2-hydroxyethyl acrylate, add them to 3 mL of isooctyl acrylate, stir evenly, then add 10 mg of azobisisobutyronitrile, and put the resulting mixed solution into 60 o The mixture was reacted in an oil bath for 30 min, the viscosity was controlled at 5000-15000 cps, and the heating was stopped to obtain an anionic polymer.
[0032] Step 2, synthesis of nano boron nitride, specifically: Take 5g of boric acid and 30g of urea and add them to 100mL of a mixture of methanol and water (v:v=1:1) and heat the mixture to 80 o C to fully dissolve the raw materials, continue stirring and reacting for 20 minutes, filter while hot after the reaction is completed, and let the collected solution stand for 48 hours after cooling to precipitate white solid. Then filter, 0 o Wash with ice water at 45°C o After drying overnight at 370 °C, white crystals were obtained. The obtained white crystals were ground in a mortar for 10 min, then placed in a tube furnace, and the temperature was gradually raised from room temperature to 900 °C in an ammonia carrier gas. o C (heating rate is 10 o C / min), the temperature reaches 900 o C and then kept warm for 3h, and then the sample was cooled to room temperature in the furnace to obtain nano boron nitride.
[0033] Step 3, the synthesis of high thermal conductivity antistatic adhesive, specifically: take 0.3g of anionic polymer and disperse it in 2mL of aqueous solution, then add 1.2g of nano boron nitride, stir evenly to obtain a polymer solution. Then take 0.2g of aluminum chloride and dissolve it in 2mL of water to obtain an aluminum chloride solution, add the aluminum chloride solution drop by drop to the polymer solution, and stir at room temperature while adding, and the dropping time is 30min. Then add 10mg of BPO and continue stirring at room temperature for 2h to obtain a high thermal conductivity antistatic adhesive for standby use.
[0034] Step 4, synthesis of antistatic adhesive, specifically: take 2 mL of benzyl vinyl trimethyl ammonium chloride, 0.5 mL of glycerol triacrylate, 1 mL of ethylene glycol phenyl ether acrylate and 1 mL of 2-hydroxyethyl acrylate, add them to 1 mL of isooctyl acrylate, stir evenly and then add 10 mg of azobisisobutyronitrile. Put the obtained mixed solution into 60 o The reaction was carried out in a C oil bath for 60 minutes, the viscosity was controlled at 20000-30000 cps, and the heating was stopped to obtain an antistatic polymer. The antistatic polymer was dispersed in 2 mL of aqueous solution, and then 10 mg of BPO was added and stirred at room temperature for 2 hours to obtain an antistatic adhesive for use.
[0035] Step 5, preparation of the tape, specifically: Take a 10x10cm PET substrate, first, apply a layer of antistatic adhesive on the lower surface of the PET substrate with a coating thickness of 20um, and then o C for 1 h and 365 nm UV light for 90 s. Then, a layer of silicone release agent (thickness 10 μm) was coated on the upper surface of the PET substrate. o Finally, a high thermal conductivity antistatic adhesive was coated on the upper surface of the release layer with a coating thickness of 50 μm and heated at 45 o C and dried for 1 hour to form an antistatic thermal conductive layer to obtain an adhesive tape.
[0036] Comparative Example 3 (Anionic nano-boron nitride was replaced with polymethyl methacrylate-modified nano-boron nitride, which could not be dispersed in water, and the preparation of the high thermal conductivity antistatic adhesive failed) Step 1, synthesis of anionic polymer, specifically: Take 0.5 g of vinyl benzoic acid, 0.5 mL of acrylic acid, 0.05 mL of triacrylate, 2 mL of ethylene glycol phenyl ether acrylate and 2 mL of 2-hydroxyethyl acrylate, add them to 3 mL of isooctyl acrylate, stir evenly and then add 10 mg of azobisisobutyronitrile. Put the resulting mixed solution into 60 oThe mixture was reacted in an oil bath for 30 min, the viscosity was controlled at 5000-15000 cps, and the heating was stopped to obtain an anionic polymer.
[0037] Step 2, synthesis of polymethyl methacrylate modified nano boron nitride, specifically: Take 5g of boric acid and 30g of urea and add them to 100mL of a mixture of methanol and water (v:v=1:1) and heat the mixture to 80 o C to fully dissolve the raw materials, continue stirring and reacting for 20 minutes, filter while hot after the reaction is completed, and let the collected solution stand for 48 hours after cooling to precipitate white solid. Then filter, 0 o Wash with ice water at 45°C o After drying overnight at 370 °C, white crystals were obtained. The obtained white crystals were ground in a mortar for 10 min, then placed in a tube furnace, and the temperature was gradually raised from room temperature to 900 °C in an ammonia carrier gas. o C (heating rate is 10 o C / min), the temperature reaches 900 o C and then kept warm for 3 hours, and then the sample was cooled to room temperature with the furnace to obtain nano boron nitride. 0.5g of nano boron nitride was dispersed in 20mL of anhydrous tetrahydrofuran solution, and then 0.05g of sodium naphthalene was added, and the nano boron nitride was activated by stirring in nitrogen and ice water bath for 24h, and 1mL of methyl methacrylate monomer was further added, and stirring was continued for 36h to obtain polymethyl methacrylate modified nano boron nitride.
[0038] Step 3, synthesis of high thermal conductivity antistatic adhesive (failure).
[0039] Comparative Example 4 (High thermal conductivity antistatic adhesive without adding anionic polymer, viscosity and antistatic performance decreased) Step 1, synthesis of anionic nano boron nitride, specifically: Take 5g of boric acid and 30g of urea and add them to 100mL of a mixture of methanol and water (v:v=1:1) and heat the mixture to 80 o C to fully dissolve the raw materials, continue stirring and reacting for 20 minutes, filter while hot after the reaction is completed, and let the collected solution stand for 48 hours after cooling to precipitate white solid. Then filter, 0 o Wash with ice water at 45°C o After drying overnight at 370 °C, white crystals were obtained. The obtained white crystals were ground in a mortar for 10 min, then placed in a tube furnace, and the temperature was gradually raised from room temperature to 900 °C in an ammonia carrier gas. o C (heating rate is 10 o C / min), the temperature reaches 900 oC and then kept warm for 3 hours, and then the sample was cooled to room temperature with the furnace to obtain nano boron nitride. 0.5g of nano boron nitride was dispersed in 20mL of anhydrous tetrahydrofuran solution, and then 0.05g of sodium naphthalene was added, and the nano boron nitride was activated by stirring in nitrogen and ice water bath for 24 hours, and 1mL of sodium acrylate monomer was further added, and stirring was continued for 36 hours. Polyacrylic acid modified nano boron nitride, also known as anionic nano boron nitride, was obtained.
[0040] Step 2, synthesis of high thermal conductivity antistatic adhesive, specifically: Take 1.2g of anionic nano-boron nitride and disperse it in 2mL of aqueous solution, and stir it evenly to obtain anionic nano-boron nitride solution; then take 0.2g of aluminum chloride and dissolve it in 2mL of water to obtain aluminum chloride solution, and add the aluminum chloride solution drop by drop to the anionic nano-boron nitride solution, stirring at room temperature while adding, and the dropping time is 30min. Then add 10mg of BPO and continue stirring at room temperature for 2h to obtain a high thermal conductivity antistatic adhesive for standby use.
[0041] Step 3, the synthesis of the antistatic adhesive, specifically: Take 2 mL of benzyl vinyl trimethyl ammonium chloride, 0.5 mL of glycerol triacrylate, 1 mL of ethylene glycol phenyl ether acrylate, and 1 mL of 2-hydroxyethyl acrylate, add them to 1 mL of isooctyl acrylate, stir evenly, and then add 10 mg of azobisisobutyronitrile. Put the resulting mixed solution into 60 o The reaction was carried out in a C oil bath for 60 minutes, the viscosity was controlled at 20000-30000 cps, and the heating was stopped to obtain an antistatic polymer. The antistatic polymer was dispersed in 2 mL of aqueous solution, and then 10 mg of BPO was added and stirred at room temperature for 2 hours to obtain an antistatic adhesive for use.
[0042] Step 4, preparation of the tape, specifically: Take a 10x10cm PET substrate, first, apply a layer of antistatic adhesive on the lower surface of the PET substrate with a coating thickness of 20um, and then o C for 1 h and 365 nm UV light for 90 s. Then, a layer of silicone release agent (thickness 10 μm) was coated on the upper surface of the PET substrate. o Finally, a high thermal conductivity antistatic adhesive was coated on the upper surface of the release layer with a coating thickness of 50 μm and heated at 45 o C for 1 h to obtain an adhesive tape.
[0043] Comparative Example 5 (When the antistatic adhesive is synthesized, benzyl vinyl trimethyl ammonium chloride is replaced with styrene, and the antistatic performance of the antistatic layer becomes weaker) Step 1, synthesis of anionic polymer, specifically: Take 0.5 g of vinyl benzoic acid, 0.5 mL of acrylic acid, 0.05 mL of triacrylate, 2 mL of ethylene glycol phenyl ether acrylate and 2 mL of 2-hydroxyethyl acrylate, add them to 3 mL of isooctyl acrylate, stir evenly, add 10 mg of azobisisobutyronitrile, and put the resulting mixed solution into 60 o The mixture was reacted in an oil bath for 30 min, the viscosity was controlled at 5000-15000 cps, and the heating was stopped to obtain an anionic polymer.
[0044] Step 2, synthesis of anionic nano boron nitride, specifically: Take 5g of boric acid and 30g of urea and add them to 100mL of a mixture of methanol and water (v:v=1:1) and heat the mixture to 80 o C to fully dissolve the raw materials, continue stirring and reacting for 20 minutes, filter while hot after the reaction is completed, and let the collected solution stand for 48 hours after cooling to precipitate white solid. Then filter, 0 o Wash with ice water at 45 o After drying overnight at 370 °C, white crystals were obtained. The obtained white crystals were ground in a mortar for 10 min, then placed in a tube furnace, and the temperature was gradually raised from room temperature to 900 °C in an ammonia carrier gas. o C (heating rate is 10 o C / min), the temperature reaches 900 o C and then kept warm for 3 hours, and then the sample was cooled to room temperature with the furnace to obtain nano boron nitride. 0.5g of nano boron nitride was dispersed in 20mL of anhydrous tetrahydrofuran solution, and then 0.05g of sodium naphthalene was added, and the nano boron nitride was activated by stirring in nitrogen and ice water bath for 24 hours, and 1mL of sodium acrylate monomer was further added, and stirring was continued for 36 hours. Polyacrylic acid modified nano boron nitride, also known as anionic nano boron nitride, was obtained.
[0045] Step 3, synthesis of high thermal conductivity antistatic adhesive, specifically: Take 0.3g of anionic polymer and disperse it in 2mL of aqueous solution, then add 1.2g of anionic nano boron nitride and stir evenly to obtain a polymer solution. Then take 0.2g of aluminum chloride and dissolve it in 2mL of water. Add the aluminum chloride solution drop by drop to the polymer solution, stirring at room temperature while adding, and the dropping time is 30min. Then add 10mg of BPO and continue stirring at room temperature for 2h to obtain a high thermal conductivity antistatic adhesive for standby use.
[0046] Step 4, the synthesis of the antistatic adhesive, is specifically: Take 2 mL of styrene, 0.5 mL of triacrylate, 1 mL of ethylene glycol phenyl ether acrylate and 1 mL of 2-hydroxyethyl acrylate, add them to 1 mL of isooctyl acrylate, stir evenly and then add 10 mg of azobisisobutyronitrile. o The reaction was carried out in a C oil bath for 60 minutes, the viscosity was controlled at 20000-30000 cps, and the heating was stopped to obtain an antistatic polymer. The antistatic polymer was dispersed in 2 mL of aqueous solution, and then 10 mg of BPO was added and stirred at room temperature for 2 hours to obtain an antistatic adhesive for use.
[0047] Step 5, preparation of the tape, specifically: Take a 10x10cm PET substrate, first, apply a layer of antistatic adhesive on the lower surface of the PET substrate with a coating thickness of 20um, and then o C for 1 h and 365 nm UV light for 90 s. Then, a layer of silicone release agent (thickness 10 μm) was coated on the upper surface of the PET substrate. o Finally, a high thermal conductivity antistatic adhesive was coated on the upper surface of the release layer with a coating thickness of 50 μm and heated at 45 o C and dried for 1 h to obtain an adhesive tape.
[0048] The properties of the adhesive tapes prepared in Example 1 and Comparative Examples 1 to 5 are shown in Table 1 below: Table 1
[0049] The peel strength is measured according to the national standard GB / T2792-2014 (180 o Under the condition), the thermal conductivity of the colloid on the tape surface is measured by a thermal conductivity tester, and the resistivity tester is used to test the resistivity of the tape surface; Compared with Example 1, in the preparation process of the tape in Comparative Example 1, AlCl3 was not added, the resistivity of the antistatic thermal conductive layer of the tape increased, the antistatic performance decreased, and the peel strength decreased.
[0050] In Comparative Example 2, the nano boron nitride was not anion modified. Compared with Example 1, the viscosity of the antistatic thermal conductive layer was greatly reduced; since the boron nitride was not modified, the nanoparticles were easily aggregated, resulting in reduced thermal conductivity. On the contrary, after the nano boron nitride in Example 1 was anion modified, electrostatic repulsion existed between the nanoparticles, effectively preventing aggregation.
[0051] In Comparative Example 3, the anionic nano-boron nitride was replaced with polymethyl methacrylate-modified nano-boron nitride. The polymethyl methacrylate-modified nano-boron nitride could not be dispersed in water, and the preparation of the high thermal conductivity antistatic adhesive failed.
[0052] In Comparative Example 4, the high thermal conductivity antistatic adhesive does not contain anionic polymers, and the viscosity is most significantly reduced. This is mainly because the anionic polymer is an acrylic adhesive resin, which has good viscosity, and the lack of anionic polymers in Comparative Example 4 leads to a significant reduction in viscosity. Similarly, the lack of anionic polymers and the lack of anions (low conductivity) lead to a reduction in the antistatic performance of the (antistatic thermal conductive layer).
[0053] When the antistatic adhesive in Comparative Example 5 is synthesized, benzyl vinyl trimethyl ammonium chloride is replaced with styrene, and the antistatic performance of the antistatic layer is weakened, mainly due to the lack of conductive ions and a significant increase in resistivity.
[0054] In order to study the thermal stability of antistatic and high thermal conductive tapes, thermogravimetric analysis was performed on the high thermal conductive antistatic adhesives in Example 1 and Comparative Examples 1, 2, and 4 (the preparation of the tape in Comparative Example 3 failed, and Comparative Example 5 was the same as the high thermal conductive antistatic adhesive in Example 1, so it was not studied).
[0055] like Figure 2 As shown in the figure, as the temperature rises, the substance decomposes. The vertical axis is the weight of the remaining after heating and decomposition. Example 1 and Comparative Examples 1, 2, and 4 are at 100 o There is a slight mass loss before 160°C, which is mainly caused by the volatilization of volatile solvents, water, etc. The initial decomposition temperature of the material in Comparative Example 4 reaches 160°C. o C or above, which is conducive to its application in high thermal conductivity materials. o After C, the final ash of Comparative Examples 1 and 2 is mainly graphitized carbon and oxidized aluminum oxide. The residual ash of Comparative Example 1 is less, mainly due to the lack of aluminum oxide components. In addition, the residual ash of Comparative Example 4 is high, mainly due to the lack of anionic polymers, which indirectly increases the aluminum and nano-boron nitride components. Compared with Comparative Examples 1, 2, and 4, Example 1 has better antistatic and thermal conductivity, as well as higher peel strength.
[0056] Example 2 The method for making the antistatic and high thermal conductive tape of the present invention specifically comprises the following steps: Step 1, synthesis of anionic polymer, specifically: Take 0.8 g of vinyl benzoic acid, 0.8 mL of acrylic acid, 0.08 mL of triacrylate, 2.5 mL of ethylene glycol phenyl ether acrylate and 2.5 mL of 2-hydroxyethyl acrylate, add them to 4 mL of isooctyl acrylate, stir evenly, add 12 mg of azobisisobutyronitrile, and put the resulting mixed solution into 70 o The mixture was reacted in an oil bath for 40 minutes, the viscosity was controlled at 5000-15000 cps, and the heating was stopped to obtain an anionic polymer.
[0057] Step 2, synthesis of anionic nano boron nitride, specifically: Take 8g of boric acid and 40g of urea and add them to 150mL of a mixture of methanol and water (v:v=1:1) and heat the mixture to 90 o C to fully dissolve the raw materials, continue stirring and reacting for 25 minutes, filter while hot after the reaction is completed, and let the collected solution stand for 56 hours after cooling to precipitate white solid. Then filter, 0 o Wash with ice water at 55°C o After drying overnight at 400 °C, white crystals were obtained. The obtained white crystals were ground in a mortar for 12 min, then placed in a tube furnace and the temperature was gradually raised from room temperature to 950 °C in an ammonia carrier gas. o C (heating rate is 10 o C / min), the temperature reaches 950 o C and then kept warm for 4 hours, and then the sample was cooled to room temperature with the furnace to obtain nano boron nitride. 0.8g of nano boron nitride was dispersed in 25mL of anhydrous tetrahydrofuran solution, and then 0.08g of sodium naphthalene was added, and the nano boron nitride was activated by stirring in nitrogen and ice water bath for 36 hours, and 1.5mL of sodium acrylate monomer was further added, and stirring was continued for 42 hours. Polyacrylic acid modified nano boron nitride, also known as anionic nano boron nitride, was obtained.
[0058] Step 3, synthesis of high thermal conductivity antistatic adhesive, specifically: Take 0.5g of anionic polymer and disperse it in 2.5mL of aqueous solution, then add 2.2g of anionic nano boron nitride and stir evenly to obtain a polymer solution. Then take 0.3g of aluminum chloride and dissolve it in 3mL of aqueous solution to obtain an aluminum chloride solution, and add the aluminum chloride solution drop by drop to the polymer solution, stirring at room temperature while adding, and the dropping time is 36min. Then add 12mg of BPO and continue stirring at room temperature for 2.5h to obtain a high thermal conductivity antistatic adhesive for standby use.
[0059] Step 4, the synthesis of the antistatic adhesive, is specifically: Take 3 mL of benzyl vinyl trimethyl ammonium chloride, 0.8 mL of glycerol triacrylate, 1.5 mL of ethylene glycol phenyl ether acrylate and 1.5 mL of 2-hydroxyethyl acrylate, add them to 1.5 mL of isooctyl acrylate, stir evenly and add 12 mg of azobisisobutyronitrile. Put the resulting mixed solution into 70 o The reaction was carried out in a C oil bath for 80 minutes, the viscosity was controlled at 20000-30000 cps, and the heating was stopped to obtain an antistatic polymer. The antistatic polymer was dispersed in 2.5 mL of aqueous solution, and then 12 mg of BPO was added and stirred at room temperature for 2.5 hours to obtain an antistatic adhesive for standby use.
[0060] Step 5, preparation of the tape, specifically: Take a 10x10cm PET substrate; first, apply a layer of antistatic adhesive on the lower surface of the PET substrate with a coating thickness of 25um, and then o C for 1.5h and 365nm UV curing for 100s (to obtain an antistatic layer). Then, a layer of silicone release agent (thickness of 15um) was coated on the upper surface of the PET substrate. o Finally, a high thermal conductivity antistatic adhesive was coated on the upper surface of the release layer with a coating thickness of 55 μm and o C and dried for 1.5 hours to form an antistatic thermal conductive layer to obtain an adhesive tape.
[0061] Example 3 The method for making the antistatic and high thermal conductive tape of the present invention specifically comprises the following steps: Step 1, synthesis of anionic polymer, specifically: Take 1g of vinyl benzoic acid, 1mL of acrylic acid, 0.1mL of glyceryl triacrylate, 3mL of ethylene glycol phenyl ether acrylate and 3mL of 2-hydroxyethyl acrylate, add them to 5mL of isooctyl acrylate, stir evenly, then add 15mg of azobisisobutyronitrile, and put the resulting mixed solution into 80 o The mixture was reacted in an oil bath for 60 min, the viscosity was controlled at 5000-15000 cps, and the heating was stopped to obtain an anionic polymer.
[0062] Step 2, synthesis of anionic nano boron nitride, specifically: Take 10g of boric acid and 60g of urea and add them to 200mL of a mixture of methanol and water (v:v=1:1) and heat the mixture to 100 o C to fully dissolve the raw materials, continue stirring and reacting for 30 minutes, filter while hot after the reaction is completed, and let the collected solution stand for 72 hours after cooling to precipitate white solid. Then filter, 0 o Wash with ice water at 60 °C o C and dried overnight to obtain white crystals. The obtained white crystals were ground in a mortar for 15 min, then placed in a tube furnace and gradually heated from room temperature to 1000 °C in an ammonia carrier gas. o C (heating rate is 10 o C / min), the temperature reaches 1000 oC and then kept warm for 6 hours, and then the sample was cooled to room temperature with the furnace to obtain nano boron nitride. 1g of nano boron nitride was dispersed in 30mL of anhydrous tetrahydrofuran solution, and then 0.1g of sodium naphthalene was added, and the nano boron nitride was activated by stirring in nitrogen and ice water bath for 48h, and 2mL of sodium acrylate monomer was further added, and stirring was continued for 48h. Polyacrylic acid modified nano boron nitride, also known as anionic nano boron nitride, was obtained.
[0063] Step 3, synthesis of high thermal conductivity antistatic adhesive, specifically: Take 0.6g of anionic polymer and disperse it in 3mL of aqueous solution, then add 2.4g of anionic nano boron nitride and stir evenly to obtain a polymer solution. Then take 0.4g of aluminum chloride and dissolve it in 4mL of aqueous solution to obtain an aluminum chloride solution, and add the aluminum chloride solution drop by drop to the polymer solution, stirring at room temperature while adding, and the dropping time is 45min. Then add 15mg of BPO and continue stirring at room temperature for 3h to obtain a high thermal conductivity antistatic adhesive for standby use.
[0064] Step 4, the synthesis of the antistatic adhesive, is specifically: Take 4 mL of benzyl vinyl trimethyl ammonium chloride, 1 mL of glycerol triacrylate, 2 mL of ethylene glycol phenyl ether acrylate and 2 mL of 2-hydroxyethyl acrylate, add them to 2 mL of isooctyl acrylate, stir evenly and then add 15 mg of azobisisobutyronitrile. Put the obtained mixed solution into 80 o The reaction was carried out in a C oil bath for 120 min, the viscosity was controlled at 20000-30000 cps, and the heating was stopped to obtain an antistatic polymer. The antistatic polymer was dispersed in 3 mL of aqueous solution, and then 15 mg of BPO was added and stirred at room temperature for 3 h to obtain an antistatic adhesive for use.
[0065] Step 5, preparation of the tape, specifically: Take a 10x10cm PET substrate; first, apply a layer of antistatic adhesive on the lower surface of the PET substrate with a coating thickness of 30um, and then o C for 2 h and 365 nm UV light for 120 s (to obtain an antistatic layer). Then, a layer of silicone oil release agent (thickness 20 μm) was coated on the upper surface of the PET substrate. o Finally, a high thermal conductivity antistatic adhesive was coated on the upper surface of the release layer with a coating thickness of 60 μm and heated at 55 o C and dried for 2 h to form an antistatic thermal conductive layer to obtain an adhesive tape.
[0066] Example 4 Compared with Example 1, in step 1, the amount of vinyl benzoic acid used is 0.6 g, and the remaining steps are the same as in Example 1.
[0067] Example 5 Compared with Example 2, in step 2, the amount of boric acid used is 9 g, and the remaining steps are the same as in Example 2.
[0068] Example 6 Compared with Example 3, in step 4, the amount of glyceryl triacrylate used is 0.9 mL.
Claims
1. A method for producing an antistatic and high thermal conductive tape, characterized in that: The specific steps include: Step 1, synthesizing anionic polymer; Step 2, synthesizing anionic nano boron nitride; Step 3, synthesizing a high thermal conductivity antistatic adhesive according to the products obtained in step 1 and step 2; Step 4, synthesizing an antistatic adhesive according to the product obtained in step 3; Step 5, making a tape according to the antistatic adhesive obtained in step 4.
2. The method for making the antistatic and high thermal conductive tape according to claim 1, characterized in that: The specific process of step 1 is as follows: Take 0.5-1g of vinyl benzoic acid, 0.5-1mL of acrylic acid, 0.05-0.1mL of triacrylate, 2-3mL of ethylene glycol phenyl ether acrylate, and 2-3mL of 2-hydroxyethyl acrylate, add them to 3-5mL of isooctyl acrylate, stir evenly, then add 10-15mg of azobisisobutyronitrile to obtain a mixed solution, and put the obtained mixed solution into 60-80 o The mixture was reacted in an oil bath for 30-60 minutes, the viscosity was controlled at 5000-15000 cps, and the heating was stopped to obtain an anionic polymer.
3. The method for making the antistatic and high thermal conductive tape according to claim 1, characterized in that: The specific process of step 2 is: Step 2.1, add 5-10g of boric acid and 30-60g of urea to 100-200mL of a mixture of methanol and water, and heat the mixture to 80-100°C. o C, stirring, reacting for 20-30 min, filtering while hot after the reaction is completed, cooling the collected solution, and standing for 48-72 h to precipitate a white solid; Step 2.2, the product obtained in step 2.1 is filtered, and o Wash with ice water at 45-60 °C o C was dried overnight to obtain white crystals; Step 2.3, grind the white crystals obtained in step 2.2 in a mortar for 10-15 minutes, then put them into a tube furnace and gradually raise the temperature from room temperature to 900-1000 °C in ammonia carrier gas. o C, the temperature reaches 900-1000 o C and then kept warm for 3-6 h, and then the sample was cooled to room temperature in the furnace to obtain nano boron nitride; Step 2.4, disperse 0.5-1g of nano-boron nitride in 20-30 mL of anhydrous tetrahydrofuran solution, then add 0.05-0.1g of sodium naphthyl, stir in nitrogen and ice water bath for 24-48h to activate the nano-boron nitride, add 1-2mL of sodium acrylate monomer, and continue stirring for 36-48h to obtain polyacrylic acid modified nano-boron nitride, also called anionic nano-boron nitride.
4. The method for making the antistatic and high thermal conductive tape according to claim 1, characterized in that: The specific process of step 3 is as follows: Step 3.1, taking 0.3-0.6 g of anionic polymer and dispersing it in 2-3 mL of aqueous solution, then adding 1.2-2.4 g of anionic nano-boron nitride, stirring evenly to obtain a polymer solution; Step 3.2, dissolving 0.2-0.4 g of aluminum trichloride in 2-4 mL of an aqueous solution to obtain an aluminum trichloride solution; Step 3.3, add the aluminum chloride solution obtained in step 3.2 dropwise to the polymer solution obtained in step 3.1, stirring at room temperature while adding, the dropping time is 30-45 minutes, and then add 10-15 mg of BPO and continue stirring at room temperature for 2-3 hours to obtain a high thermal conductive antistatic adhesive.
5. The method for making the antistatic and high thermal conductive tape according to claim 1, characterized in that: The specific process of step 4 is: dispersing the antistatic polymer in 2-3 mL of aqueous solution, then adding 10-15 mg of BPO and continuing to stir at room temperature for 2-3 hours to obtain an antistatic adhesive.
6. The method for making the antistatic and high thermal conductive tape according to claim 5, characterized in that: In step 4, the preparation process of the antistatic polymer is as follows: 2-4 mL of benzyl vinyl trimethyl ammonium chloride, 0.5-1 mL of glycerol triacrylate, 1-2 mL of ethylene glycol phenyl ether acrylate and 1-2 mL of 2-hydroxyethyl acrylate are added to 1-2 mL of isooctyl acrylate, stirred evenly, and then 10-15 mg of azobisisobutyronitrile is added, and the resulting mixed solution is placed in 60-80 o The reaction was carried out in an oil bath pot C for 60-120 minutes, the viscosity was controlled at 20000-30000 cps, and the heating was stopped to obtain an antistatic polymer.
7. The method for making the antistatic and high thermal conductive tape according to claim 5, characterized in that: The specific process of step 5 is as follows: Step 5.1, a layer of antistatic adhesive prepared in step 4 is coated on the lower surface of the PET substrate with a coating thickness of 20-30um, and then the coating is passed through 60-80 o C drying for 1-2h and 365nm UV curing for 90-120s; Step 5.2, apply a layer of silicone release agent on the upper surface of the PET substrate with a thickness of 10-20um, 120-130 o C is cured to form a release layer; Step 5.3, coating the high thermal conductivity antistatic adhesive prepared in step 3 on the upper surface of the release layer prepared in step 5.2, with a coating thickness of 50-60 um, and o C and dried for 1-2 hours to form an antistatic heat-conductive layer to obtain an adhesive tape.
8. An antistatic and highly thermally conductive tape, produced by the method for producing an antistatic and highly thermally conductive tape as claimed in any one of claims 1 to 7.